STUDY ON GENETIC CHARACTERISTICS OF IN VITRO CULTURE AND INTRACELLULAR TRANSDUCTION OF EXOGENOUS FLURESCENT PROTEINS IN FIBROBLAST CELL LINE OF ANGORA GOAT - C. Q. Liu; Y. Guo; X. C. Li; T. F. Lu; W. J. Guan; Y. H. Ma (Journal of Animal and Plant Sciences, 2013)
Establishment of fibroblast cell lines of endangered goat breeds and research on the gene or protein functions based on the cells made a significant contribution to the conservation and utilization of genetic resources. In this study, a fibroblast cell line of Angora goat (AGF31) from 31 samples, frozen in 162 cryogenically-preserved vials with (2–3) ×106 cells each, was successfully established by using explants culture and cryopreservation techniques. The cells cultured in vitro showed typical morphology of fibroblasts, with a population doubling time of 34.3h; The average viability of the cells was 97.6 % before freezing and 95.9 % after thawing; Chromosome karyotyping and G-banding analysis showed that >90.8% cells were diploid (2n=60) prior to the 4th generation; Neither microbial contamination nor cross- contamination was detected by isoenzyme analyses; To determine cell permeability, intracellular path and stability of exogenous proteins during the transduction, six fluorescent protein genes were transferred into fibroblasts by lipofectamine-mediated method. The transfection efficiency of six fluorescent protein genes fluctuated between 13.4%and 60.8%. ECFP and DsRed were mostly shown in cytoplasmic in dots around the nucleus, and EYFP and EGFP had a slightly stronger expression in the nucleus than in the cytoplasm. Angora goat fibroblasts still kept stable genetic properties and normal biological characteristics in vitro, and every index met the standard quality control of American Type Culture Collection.
Keywords: Angora goat; Fibroblast cell line; Characterization; Cryopreservation